Highly Sensitive Exosome Detection for Early Diagnosis of Pancreatic Cancer Using Immunoassay Based on Hierarchical Surface‐Enhanced Raman Scattering Substrate. Issue 6 (23rd April 2022) - Li, Juan; Li, Yanru; Chen, Shuai; Duan, Weili; Kong, Xue; Wang, Yunshan; Zhou, Lianqun; Li, Peilong; Zhang, Chengpeng; Du, Lutao; Wang, Chuanxin
Abstract: Exosomes have emerged as potential biomarkers for pancreatic cancer (PaC). However, it is still challenging to get quantitative detection of exosomes with the specific surface receptors. In this study, a highly sensitive detection system is first constructed for the direct quantitation of specific exosomes in real samples using hierarchical surface‐enhanced Raman scattering substrate (H‐SERS substrate) and rapid enrichment strategy magnetic beads @ exosomes @ SERS detection probes (MEDP). It is found that the detection system (MEDP @ H‐SERS substrate) could provide a 3.5 times higher SERS intensity compared with MEDP sandwich immunocomplex only. Moreover, LRG1‐positive exosomes (LRG1‐Exos) and GPC1‐positive exosomes (GPC1‐Exos) are chosen to distinguish PaC through exosome proteomics and database screening. The lower limit of detection (LOD) is 15 particles µL ‐1 using the MEDP @ H‐SERS substrate. Significantly, the detection in clinical samples shows that the innovative combination of LRG1‐Exos and GPC1‐Exos could improve the diagnostic efficiency of PaC, with an area under the operating characteristic curve (AUC) of 0.95. Even for the early‐stage PaC, the diagnostic accuracy is still high (AUC = 0.95). Collectively, the findings indicate that the MEDP @ H‐SERS substrate has great potential for the early diagnosis of PaC. Abstract : A highly sensitive detection system is firstly constructed for the direct quantitation of LRG1‐positive exosomes and GPC1‐positive exosomes in serum samples using hierarchical surface‐enhanced Raman scattering substrate (H‐SERS substrate) and rapid enrichment strategy magnetic beads @ exosomes @ SERS detection probes (MEDP). The MEDP @ H‐SERS substrate has great potential for the early diagnosis of pancreatic cancer.